Exchange of short-chain oxygenated volatile organic compounds (VOCs) between plants and the atmosphere: A compilation of field and laboratory studies - Kesselmeier, J (Journal of Atmospheric Chemistry, 2001)
Field and laboratory investigations of the exchange of the short-chain organic acids – formic acid and acetic acid – as well as their homologous aldehydes are discussed. Both acids are substantially released from several plant species. Emission measurements under ﬁeld conditions are compiled to give an overview of three years of measurements. Emission rates from several tree species were found in the range between zero and 60 nmoles m−2 min−1 for acetic acid and between zero and 90 nmoles m−2 min−1 for formic acid though also a deposition has been observed to orange trees. Investigations under laboratory conditions showed an order of magnitude lower emission rates with signiﬁcant differences under light and dark conditions, and a deposition was observed under certain conditions. Hence, low emission rates or even a bi-directional exchange, emission as well as deposition have to be taken into account. Further differences between ﬁeld and laboratory studies are discussed considering age of trees, stress effects and a potential production of acids by photochemical conversion of precursors inside enclosures during sampling. Field data on the exchange of formand acetaldehyde show a complex behavior. We found emission as well as uptake. The bi-directional exchange is signiﬁcantly triggered by the ambient mixing ratios of both aldehyde species and exhibits a compensation point. Further studies are needed for generalization of the exchange of these and potentially also for other compounds
Keywords: Acetaldehyde; acetic acid; biogenic deposition; Biogenic emission; carbonyls; compensation point; Formaldehyde; formic acid; organic acids; Volatile Organic Compounds

Apoplastic Solute Concentrations of Organic Acids and Mineral Nutrients in the Leaves of Several Fagaceae - Gabriel, Reinhard; Kesselmeier, Jürgen (Plant and Cell Physiology, 1999)
Ion chromatographic methods determined organic acids and main nutrient minerals in the apoplastic solution from leaves of several Fagaceae (Quercus ilex L., Quercus cerris L., Quercus virgiliana (Ten.) Ten, and Fagus sylvatica L.). The anions of organic acids found in high amounts (250 to 650 μM) were quinate, malate, and oxalate. Lactate, pyruvate, formate and acetate were detected in relatively low amounts with concentrations between 20 and 200 μM. The total concentration of organic acids in the apoplastic sap ranged between 1.5 and 2 mM. The total concentration of inorganic cations (K+, Mg2+, NH4+, Ca2+, Na+) and anions (C1−, NO3−, SO2−4 and PO3−4) in the apoplastic sap varied between 5 and 10 mM, and 0.35 and 1.8 mM, respectively. We conclude that the concentration of organic acid ions in the leaf apoplast depends mainly on the exchange with the leaf cells and is influenced by the electrochemical gradient between the symplast and the apoplast in relation to the water potential of the leaf. The determination of formate and acetate in the apoplastic compartment of leaves lend weight to the argument that the production of these acids by trees is a important emission source to the atmosphere.
Keywords: Anions; Apoplast; cations; Fagaceae; leaf; organic acids

Apoplastic Solute Concentrations of Organic Acids and Mineral Nutrients in the Leaves of Several Fagaceae - Gabriel, Reinhard; Kesselmeier, Jürgen (Plant and Cell Physiology, 1999)
Ion chromatographic methods determined organic acids and main nutrient minerals in the apoplastic solution from leaves of several Fagaceae (Quercus ilex L., Quercus cerris L., Quercus virgiliana (Ten.) Ten, and Fagus sylvatica L.). The anions of organic acids found in high amounts (250 to 650 μM) were quinate, malate, and oxalate. Lactate, pyruvate, formate and acetate were detected in relatively low amounts with concentrations between 20 and 200 μM. The total concentration of organic acids in the apoplastic sap ranged between 1.5 and 2 mM. The total concentration of inorganic cations (K+, Mg2+, NH4+, Ca2+, Na+) and anions (C1−, NO3−, SO2−4 and PO3−4) in the apoplastic sap varied between 5 and 10 mM, and 0.35 and 1.8 mM, respectively. We conclude that the concentration of organic acid ions in the leaf apoplast depends mainly on the exchange with the leaf cells and is influenced by the electrochemical gradient between the symplast and the apoplast in relation to the water potential of the leaf. The determination of formate and acetate in the apoplastic compartment of leaves lend weight to the argument that the production of these acids by trees is a important emission source to the atmosphere.
Keywords: Anions; Apoplast; cations; Fagaceae; leaf; organic acids

Factors controlling the emissions of volatile organic acids from leaves of Quercus ilex L.(Holm oak) - Gabriel, R.; Schäfer, L.; Gerlach, C. (Atmospheric Environment, 1999)
Direct emissions and emission of precursor compounds of acetic and formic acid from higher plants are a signiÞcant source of these acids in the atmosphere. To travel from the plant cell to the atmosphere, a gas molecule must Þrst leave the liquid phase and then enter the internal leaf gas phase. The apoplast (cell wall) is the last barrier before the molecule can escape through the stomata. During Þeld experiments we monitored the gas exchange (H 2 O, CO 2 , organic acids) of Quercus ilex L. leaves. The exchange rates of acetic and formic acid under Þeld conditions followed a typical diurnal pattern and ranged between!10 (uptake) and 52 (emission) nmol m~2 leaf area min~1 with the maximum around noon. Growth chamber experiments indicate that the emission is related to the stomatal conductance. We discussed the exchange rate of organic acids between the cell wall and the atmosphere in connection with HenryÕs law, and the physicochemical conditions in the cell wall. The evaluation showed that for apoplastic pH values between 4 and 5, 26Ð130% of the measured acetic acid emission based on leaf area could be predicted. ( 1999 Elsevier Science Ltd. All rights reserved.
Keywords: aba abscisic acid; Gas exchange; organic acids; Quercus ilex

Factors controlling the emissions of volatile organic acids from leaves of Quercus ilex L.(Holm oak) - Gabriel, R; Schafer, L; Gerlach, C (Atmospheric Environment, 1999)
Direct emissions and emission of precursor compounds of acetic and formic acid from higher plants are a signiÞcant source of these acids in the atmosphere. To travel from the plant cell to the atmosphere, a gas molecule must Þrst leave the liquid phase and then enter the internal leaf gas phase. The apoplast (cell wall) is the last barrier before the molecule can escape through the stomata. During Þeld experiments we monitored the gas exchange (H 2 O, CO 2 , organic acids) of Quercus ilex L. leaves. The exchange rates of acetic and formic acid under Þeld conditions followed a typical diurnal pattern and ranged between!10 (uptake) and 52 (emission) nmol m~2 leaf area min~1 with the maximum around noon. Growth chamber experiments indicate that the emission is related to the stomatal conductance. We discussed the exchange rate of organic acids between the cell wall and the atmosphere in connection with HenryÕs law, and the physicochemical conditions in the cell wall. The evaluation showed that for apoplastic pH values between 4 and 5, 26Ð130% of the measured acetic acid emission based on leaf area could be predicted. ( 1999 Elsevier Science Ltd. All rights reserved.
Keywords: aba abscisic acid; Gas exchange; organic acids; Quercus ilex

Exchange of atmospheric formic and acetic acids with trees and crop plants under controlled chamber and purified air conditions - Kesselmeier, J; Bode, K; Gerlach, C; Jork, E.-M (Atmospheric Environment, 1998)
We investigated the exchange of formic and acetic acids between the atmosphere and various tree species such as beech (Fagus sylvatica L.), ash (Fraxinus excelsior L.), spruce (Picea abies L.) Karst, holm oak (Quercus ilex L.), and birch (Betula pendula L.). and some crop-plant species such as corn (Zea mays, var. Banjo), pea (Pisum sativum, var. Solara), barley (Hordeum vulgare, var. Igri) and oat (Avena sativa, var. Wiesel). All experiments were done with dynamic enclosures ßushed with puriÞed oxidant-free air, containing only low or controlled amounts of the two acids. SigniÞcant and light-triggered emission of both acids from all tree species was observed. For one tree species (ash) a seasonal large increase in fall due to early leaf decomposition was found. The standard emission factors (30¡C and PAR"1000 kmol m2 s~1) given as (nmol m~2 min~1) for acetic and formic acids, respectively, were 8.1 and 29.7 (ash, autumn), 1.0 and 3.3 (ash, summer), 0.9 and 1.4 (beech), 0.7 and 1.45 (spruce), 1.9 and 2.4 (Holm oak) and 1.7 and 6.7 (birch). Rough estimation of global annual emissions range between 20 and 130 Gmol formic acid and 10 and 33 Gmol acetic acid. These numbers reßect a 15Ð30% contribution by forest emissions to the continental organic acid budget. As compared to the global total NMHC emissions low molecular weight organic acids are of minor importance. In contrast to the trees, none of the crop-plant species investigated showed an emission, but always a clear deposition of both acids. Both emission from trees as well as uptake by the agricultural plants could be related to transpiration rates and leaf conductances
Keywords: acetic acid; assimilation; Atmosphere; crop plants; exchange of volatile organic compounds; formic acid; leaf conductance; organic acids; Plants; Transpiration; Trees

EMISSION OF SHORT CHAINED ORGANIC ACIDS , ALDEHYDES AND MONOTERPENES FROM QUERCUS ILEX L . AND PINUS PINEA L . IN RELATION TO PHYSIOLOGICAL ACTIVITIES , CARBON BUDGET AND EMISSION ALGORITHMS - Kesselmeier, J; Bode, K; Hofmann, U; Mtjller, H; Schafer, L; Wolf, A; Ciccioli, P; Cecinato, A; Frattoni, M; Foster, P; Dutaur, L; Torreq, L (Atmospheric Environment, 1997)
We report on the emission of monoterpenes, short-chained organic acids and aldehydes from Mediterranean oak (Quercus ilex L.) and pine (Pinus pinea L.). All studies were done with dynamic cuvettes enclosing intact branches at the top of the canopy flushed with ambient air. Daily trends are compared with the photosynthetic active radiation (PAR), leaf temperature and the physiological activities of the enclosed branches, i.e. assimilation and transpiration, with special attention on the carbon budget. Oak emits monoterpenes in high amounts, up to 2% of the assimilated carbon. As compared with monoterpenes, short-chained organic acids and aldehydes are of minor importance for oak. However, on a leaf dry-weight basis equal amounts of acids and aldehydes are released from oak and pine. As pine emitted only low amounts of terpenes (below 0.2% of the assimilated carbon) the release of terpenes and oxygenated compounds is of equal importance for this species. A comparison of a modelled light and temperature driven emission with the observed volatile organic compounds (VOC) emissions showed good agreement for monoterpenes as well as for organic acids emitted in the case of oak. For pine only the release of acids showed an adequate relation to the algorithm data, whereas the terpene emissions seemed to be dominated by temperature effects
Keywords: aldehydes; carbon budget; coniferous; deciduous; light; Monoterpenes; oak; organic acids; pine; Pinus pinea L; Plant physiology; Quercus ilex L; Temperature; Volatile Organic Compounds